Expert consensus on the diagnosis and therapy of endo-periodontal lesions - Bin Chen; Yanan Zhu; Minkui Lin; Yangheng Zhang; Yanfen Li; Xiangying Ouyang; Song Ge; Jiang Lin; Yaping Pan; Yan Xu; Yi Ding; Shaohua Ge; et al. (Nature Publishing Group, 2024)
Abstract Endo-periodontal lesions (EPLs) involve both the periodontium and pulp tissue and have complicated etiologies and pathogenic mechanisms, including unique anatomical and microbiological characteristics and multiple contributing factors. This etiological complexity leads to difficulties in determining patient prognosis, posing great challenges in clinical practice. Furthermore, EPL-affected teeth require multidisciplinary therapy, including periodontal therapy, endodontic therapy and others, but there is still much debate about the appropriate timing of periodontal therapy and root canal therapy. By compiling the most recent findings on the etiology, pathogenesis, clinical characteristics, diagnosis, therapy, and prognosis of EPL-affected teeth, this consensus sought to support clinicians in making the best possible treatment decisions based on both biological and clinical evidence.